Nurse Residency Programs and the Transition to Child Health Nursing Practice. (June 2015) - Delack, Sandi; Martin, Jean; McCarthy, Ann Marie; Sperhac, Arlene M.
<x xml:space="preserve">Abstract</x> Nurse residency programs for newly licensed RNs are a critical component in bridging the clinical practice gap between education and practice. In May 2013, the Institute of Pediatric Nursing invited leaders from pediatric nursing organizations and children's hospitals to attend a forum on nurse residency programs for pediatric nurses. This article presents a summary of the discussions that occurred during the forum and makes recommendations for addressing issues related to nurse residency programs.